From “Yojo-Han” Art Center to “Untitled School of Arts”: the possibility of a local art education network developing from a bedroom-sized art center / Ko Yamada and Takuji Okagawa - Yamada, Ko; Okagawa, Takuji (Universiti Teknologi MARA, Perak, 2018)
In 2012, the alternative art center “Yojo-Han”, named after the popular 8.25 ㎡ unit size of old Japanese bed-sits, was established. It is located in an art and design building in central Nagoya, in a venue of Aichi Triennale. The unit “yojohan” symbolizes bed-sits for young people and their ambitions from the 1950's to the 80's. This name was chosen to attract visitors and students in the prime of their life. Unlike NPO-run large facilities demanding much maintenance, the art center is a small and semi-private space for public art education activities. There are four directors with equal authority for this small institution. Through wellorganized scheduling, this tiny space transforms into a photography school, poetry seminar, sculpture school, graduate-level digital seminar, various workshops, streaming radio station, and other events. Most activities are weekly and open to the public. As with smart phone applications, each activity occupies the whole center when held and “Yojo-han” becomes the individual school/workshop. This paper introduces the center's activities, summarizing this format's function and its social importance in public art education. Furthermore, the concept of local networks of such unique art schools as an “Untitled School of Arts” is introduced as a system to facilitate sustainable public art education.